Peran Fungsi Eksekutif terhadap Penggunaan Strategi Regulasi Emosi Remaja - Alifia Nafasa Budianto; Rini Setyowati (UNS Press, 2025)
Adolescence is a period that requires learning in emotion regulation, because at this time adolescents experience fundamental changes, especially in emotional aspects. Emotion regulation can be done with two strategies, namely cognitive reappraisal and expressive suppression. One of the factors that influences emotion regulation is executive function, which is a neurocognitive process that plays a role in the integration of information and emotions. Therefore, this study aims to look at the role of executive function in using adolescent cognitive reappraisal and expressive suppression strategies. The study was a descriptive correlational study with a sample of 225 adolescents living in Indonesia aged 13-17 years who were involved through convenience sampling techniques. The measuring instruments used in this study were the Emotion Regulation Questionnaire (ERQ) with a reliability value of 0.951 for CR and 0.790 for ES, and the Executive Skills Questionnaire-Revised (ESQ-R) with a reliability value of 0.897. The results of the study, analyzed using simple linear regression techniques, show that executive function plays a positive role in predicting the use of cognitive reappraisal and expressive suppression strategies, with a correlation value of 0.513 and 0.257. This study found the importance of executive function in influencing the use of emotion regulation strategies in adolescents. Thus, improving executive functions (such as organization, time management, response inhibition, emotional control, sustained action, and goaldirected persistence) can contribute to an individual's ability to manage emotions more adaptively